Reliability of RC shear walls with uncertainty of failure mode - ICASP14; Xiang, Dong; Gao, Xiangling (My University, 2023)
The propagation of damage evolution at different scales leads to the uncertainty of failure mode for shear walls, and it is difficult to determine the reliability of shear walls with shear failure accurately using the threshold value of flexural failure. In this study, the feasibility of three-parameter kinematic theory for shear-dominated reinforced concrete shear walls is validated by the shear capacity of 27 RC shear walls and the lateral load-displacement curves of 8 RC shear walls. The deterministic and stochastic parametric analysis of shear walls’ nonlinear behavior are conducted, and the results indicate that multiple failure modes occur in shear walls with compressive strength of concrete 44-64MPa. Finally, the damage state is chosen as the failure threshold, and the calculation results indicate that the reliability of RC shear walls under major earthquake was improved by increasing the compressive strength of concrete.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED